Playgroups as a setting for nutrition and physical activity interventions for mothers with young children: exploratory qualitative findings - Jones, Carlie; Burns, Sharyn; Howat, Peter; Jancey, Jonine; McManus, Alexandra; Carter, Owen (Australian Health Promotion Association, 2010)
Issue addressed: The child bearing years are associated with increased risk of weight gain for many women. Little is known about the attitudes and preferences for nutrition and physical activity interventions in this population. This research investigated the barriers and facilitators of mothers with young children to engage in healthy physical activity and nutrition behaviours. Methods: Eight focus groups were conducted with mothers (n=65) who attend Perth, metropolitan playgroups. Transcriptions from the groups plus observer notes were used to conduct a thematic analysis. Results: Participants were aware of the need for good nutrition and adequate physical activity but many failed to meet public health recommendations. Many participants were keen to improve their diet and increase their levels of physical activity. However, a major barrier to adopting and maintaining healthy diets and adequate physical activity levels was a shift in priorities from investing in their own health to investing in their children's. Conclusions: Interventions using a 'whole family' approach are more likely to be successful in engaging mothers. Interventions should focus on strengthening mothers' self efficacy surrounding eating and physical activity.